Analisis Teknologi terhadap Perekonomian Nasional: Studi Kasus Kontribusi GoTo terhadap Pendapatan Indonesia - Abiyyu Rahmatullah; Agus Rizki Pandapotan Siagian; Ahmad Devani Yuslah; Alfia Damar Yanti; Annisa, Fesya Diva; Ahmad Setiawan Nuraya (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
The research analyzes the impact of technology on Indonesia's national economy, focusing on GoTo's contribution as a leading technology company. GoTo, born from the merger of Gojek and Tokopedia, has created an innovative business model that connects consumers and businesses through an efficient digital platform. Secondary data analysis from LPEM FEB UI (2023), Aji (2023), Jerry (2023) SMERU Research Institute (2022), and other relevant sources, shows that GoTo makes a significant contribution to Indonesia's GDP, estimated at Rp349 trillion to Rp428 trillion in 2022, equivalent to 1.8% to 2.2% of total GDP. In addition, GoTo has empowered MSMEs by increasing average incomes by 30% for those in its ecosystem, created approximately 1.7 million jobs, and contributed to reducing income inequality by lowering the Gini coefficient by 4.43% in its operating regions. The research also underscores the importance of GoTo in facilitating increased value addition and business efficiency. Nonetheless, challenges such as the digital divide and the need for increased digital literacy remain a concern. By optimally utilizing the potential of the digital ecosystem and addressing existing challenges, Indonesia can achieve sustainable, inclusive, and equitable economic growth through the strategic role of technology companies like GoTo.